Changes in the care of acute cerebrovascular and cardiovascular conditions during the first year of the covid-19 pandemic in 746 hospitals in the USA: retrospective analysis - Raul G Nogueira; Diogo C Haussen; Alhamza R Al-Bayati; Thanh N Nguyen; Charlene Wong; Rahul Khanna; Rajesh Sachdeva; Michael McDaniel; Mahmoud H Mohammaden; Bernardo Liberato; Dinesh V Jillella; Michael Frankel; et al. (BMJ Medicine)
Objective To measure the impact of the covid-19 pandemic on admissions to hospital and interventions for acute ischemic stroke and acute myocardial infarction.Design A retrospective analysis.Setting 746 qualifying hospitals in the USA from the Premier Healthcare Database.Participants Patients aged 18 years and older who were admitted to hospital with a primary diagnosis of acute ischemic stroke or acute myocardial infarction between 1 March 2019 and 28 February 2021.Main outcome measures Relative changes in volumes were assessed for acute ischemic stroke and acute myocardial infarction hospital admissions as well as intravenous thrombolysis, mechanical thrombectomy, and percutaneous coronary intervention (overall and for acute myocardial infarction only) across the first year of the pandemic versus the prior year. Mortality in hospital and length of stay in hospital were also compared across the first year of the pandemic versus the corresponding period the year prior. These metrics were explored across the different pandemic waves.Results Among 746 qualifying hospitals, admissions to hospital were significantly reduced after the covid-19 pandemic compared with before the pandemic for acute ischemic stroke (−13.59% (95% confidence interval−13.77% to −13.41%) and acute myocardial infarction (−17.20% (−17.39% to −17.01%)), as well as intravenous thrombolysis (−9.47% (−9.99% to −9.02%)), any percutaneous coronary intervention (−17.89% (−18.06% to −17.71%)), and percutaneous coronary intervention for acute myocardial infarction (−14.36% (−14.59% to −14.12%)). During the first year of the pandemic versus the previous year, the odds of mortality in hospital for acute ischemic stroke were 9.00% higher (3.51% v 3.16%; ratio of the means 1.09 (95% confidence interval (1.03 to 1.15); P=0.0013) and for acute myocardial infarction were 18.00% higher (4.81% v 4.29%; ratio of the means 1.18 (1.13 to 1.23); P<0.0001).Conclusions We observed substantial decreases in admissions to hospital with acute ischemic stroke and acute myocardial infarction, but an increase in mortality in hospital throughout the first year of the pandemic. Public health interventions are needed to prevent these reductions in future pandemics.